Digital Economy As A New Form Of Economic Relations: Evidences From Uzbekistan - Mardonova Ashirjon Tursunbayevna, Taniev Akhmadjon Bahromovich, Rahmanov Toshmurza (International Journal of Advanced Science and Technology, 2020)
This paper designations of the digital economy of diverse researchers, provides samples and identifies the definition of the digital economy. Also, research has focused on investigations of the role of the digital economy in the modern world economy, including in the economies of developing countries, the role of the Republic of Uzbekistan in supporting the digital economy and the possibility of developing the digital economy in Uzbekistan.